Development of Science Learning Tools using the STEM Approach to Train Problem Solving Ability and Students Activeness in Global Warming Material - Aulia Isatunada*; Sri Haryani (Jurnal Pendidikan Sains Indonesia, 2021)
The success of learning in schools cannot be separated from planning appropriate learning strategies and learning tools used by teachers in the classroom. The learning device is used by the teacher as a benchmark to see how far the teacher has succeeded in teaching which can be seen when a method in the learning tool is applied. This research aims to produce science learning tools using the STEM approach to train problem solving abiliy and students activeness on global warming material that is suitable for use to support the learning process. The development procedure in this research refers to the ADDIE development model. Data collection techniques obtained by the method of observation, questionnaires, and documentation. Based on the results of the research, it shows that the learning tools developed have characteristics, including: learning tools with a STEM approach so that they refer to the disciplines of science, technology, engineering, and mathematics; using leaflet media as a learning medium that is used to convey information; taking the theme of global warming as the main subject; there are indicators of problem solving abilities in the learning tools developed; and there are indicators of activity in the learning tools developed. The results of the feasibility test analysis based on the percentage of validation on the presentation and material aspects, namely the syllabus obtained a percentage of 94.60%, lesson plans obtained a percentage of 94.46%, student discussion sheet obtained a percentage of 93.50%, test questions obtained a percentage of 93.34%, the observation sheet obtained a percentage of 95.42%, and the leaflet media obtained a percentage of 97.50%. Meanwhile, the leaflet media also obtained a percentage based on the results of the student response questionnaire on the validity, practicality, and effectiveness aspects of 89.56% which means that the leaflet media is very good to be used to assist the delivery of material in the learning process. Based on this, it can be concluded that science learning tools using the STEM approach to train problem solving abiliy and students activeness on global warming material are very suitable for support the learning process